Success and Challenges of Establishing a Teledermatology Pilot Service at a Student-Run Clinic - Hannah Rashdan; Georgia E Williams; Daniel Bamrick-Fernandez; Alma Rosa Rivera; Attilie Carrig; Dayna Diven (Journal of Student-Run Clinics, 2024)
Background: Dermatologic issues are the primary reason people experiencing homelessness (PEH) seek care.1 Furthermore, the closure of clinics and shelters during the coronavirus disease 2019 (COVID-19) pandemic highlighted care disparities and the need for telehealth services.2,3 Though teledermatology is feasible and reliable, many PEH do not have access to dermatologists, often due to few dermatologists accepting public health insurance programs.4 This study investigated the challenges and successes of a teledermatology pilot within an existing student-led clinic for PEH, the diagnostic concordance between onsite primary care providers (PCP) and teledermatologists, as well as the quality of life of PEH with dermatologic issues to better understand the impact of cutaneous conditions of the unhoused.Methods: A teledermatology consultation service was established at a student-led clinic in Austin, Texas. Teleconsultations were conducted with offsite dermatology residents using a secure messaging platform. PCP diagnoses were recorded prior to the teledermatologist consultation. Patients completed the Dermatology Life Quality Index survey upon visit completion.Results: We had several successes in implementing this teledermatology pilot service, including smooth integration of the service, sustainability through cross-class collaboration, earlier in-person follow-up, and dermatologic education for PEH. However, we also encountered challenges, including limited patient volume with ongoing construction and remote site location, inadequate patient access to medication with no onsite pharmacy, and limited medical literacy.Conclusions: In this pilot program, reasonable patient volume suggests this model is sustainable for both student-led clinics and dermatology residents. PCPs can limit use of this service to diagnostic and therapeutic dilemmas given the high concordance in diagnoses. Future directions include increasing the magnitude of patients served and collaborating with the student-run clinic team to address upstream social determinants of health. We hope this pilot study provides evidence that this teledermatology model is replicable in other clinic settings and potentially with other specialties.